Practice Management - David Schwab, PhD (Blackwell Synergy, 2000)
Whether you encounter new people through your involvement with community activities such as the Rotary Club or your local Chamber of Commerce, through shared interests such as golf or attending sporting events, or through the activities of your spouse or children, every person you meet for the first time has the potential to become your patient and/or refer you a patient.